Primary graded groups with complementable non-Frattini subgroups - Dovzhenko, S. A.; Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We describe primary graded groups (in particular, locally graded, RN-groups) with complementable non-Frattini subgroups.